Estilos de crianza y conductas agresivas de los estudiantes de la Unidad Educativa “Iberoamericano” - Espinoza Merino, María Belén (2021)
This study describes the relationship between parenting styles and aggressive behavior in children.It analyzes them through the family and society where various situations in which children grow up. In parenting style, there are four types: democratic, authoritative, authoritarian, and negligent.The parental style is how parents educate their children and are in charge of imparting values. Currently, the family's role has changed, varying the style of parents and communication between parents and children, which allows inappropriate behavior to result in conflict between peers and within their family environment. The present investigation presented a quantitative approach basedon a non-experimental, cross-sectional and correlational design. For the objectives, it was basic, and for the location, it was field research. It was carried out in the "Iberoamericano" Educational Unit with an intentional non-probabilistic sample of 30 students from the seventh and eighth parallel year "A." The techniques used were the Baumrind parenting styles questionnaire and the Ad-Hoc questionnaire e, which allowed to know the students' aggressive behaviors. The results showed a significant correlation between parenting styles and aggressive behaviors that students have developed in the educational institution.